2011
DOI: 10.1590/s1516-35982011000500023
|View full text |Cite
|
Sign up to set email alerts
|

Total and partial digestibility, rates of digestion obtained with rumen evacuation and microbial protein synthesis in bovines fed fresh or ensiled sugar cane and corn silage

Abstract: -It was evaluated intake, rumen and intestinal digestibility and passage and digestion rates in bovines fed diets constituted of corn silage, crushed sugar cane and given fresh, crushed sugar cane and given after 72 hours of storage, ensiled sugar cane with 1% of calcium oxide and with no treatment and a same concentrate fixed at 1% of body weight. All roughage was corrected to contain 10% of crude protein. It was used five rumen-fistulated bovine with average weight of 240 ± 15 kg, distributed in a 5 × 5 Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Digestibility of apNDF for BGS, EGS, and T85 was greater compared with that of SC; possibly, the CP adjustment to 11% using urea was sufficient to enhance the apNDF digestibility, as recommended by Lazzarini et al (2009) for low-quality forages. According to Menezes et al (2011), the greater iNDF content found in sugarcane-based diets can also limit the total degradation of apNDF, decreasing its digestibility. Tropical forages have an accelerated process of morphological differentiation, characterized by increased sustention tissue present in the stem fraction and a reduction of tissues related to the leaf fraction as they reach maturity and consequently increase in fiber content (Nelson and Moser, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Digestibility of apNDF for BGS, EGS, and T85 was greater compared with that of SC; possibly, the CP adjustment to 11% using urea was sufficient to enhance the apNDF digestibility, as recommended by Lazzarini et al (2009) for low-quality forages. According to Menezes et al (2011), the greater iNDF content found in sugarcane-based diets can also limit the total degradation of apNDF, decreasing its digestibility. Tropical forages have an accelerated process of morphological differentiation, characterized by increased sustention tissue present in the stem fraction and a reduction of tissues related to the leaf fraction as they reach maturity and consequently increase in fiber content (Nelson and Moser, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Five non-castrated male Santa Ines sheep (34.0 ± 3.6 kg bodyweight), cannulated in the rumen, were used in a 5 x 5 Latin square experiment. Each period lasted 15 days, with the first eight days for diet adaptation (Storry & Sutton, 1969;Menezes et al, 2011), followed by seven days for data collection. Sheep were housed in individual pens with wooden floors and had free access to water.…”
Section: Methodsmentioning
confidence: 99%
“…Each experimental period (five periods) lasted 15 days, with the first eight days dedicated to animal adaptation (Storry and Sutton, 1969;Menezes et al, 2011). Voluntary intake was evaluated from the 4th to 11th day of each experimental period with samples of ingredients, orts, and feces (total collection used a collection bag attached to the animals) collected for the three consecutive days of each period.…”
Section: Methodsmentioning
confidence: 99%